Defining flows to protect instream biota : a critique of the instream flow incremental methodology and the development of a hierarchical habitat-based approach, using the pennant-tailed catlet, Chiloglanis anoterus in the Marite River, South Africa - Pollard, S (Sharon) (Department of Biological Sciences, 2014)
Bibliography: leaves 249-279.